Lockdown and Breakdown in Italians’ Reactions on Twitter during the First Phase of Covid-19 - Boccia Artieri, Giovanni; Greco, Francesca; La Rocca, Gevisa (PARTECIPAZIONE E CONFLITTO, 2021)
The article focuses on Italians’ reactions to the pandemic on Twitter. During the first phase of the 2020 lockdown (from the beginning of March 2020 - to the beginning of May 2020), a real-time dataset was built, linking data scratching to three events related to the introduction of the Prime Minister’s decrees and his press conferences. The chosen observation point is Twitter, platform that allows us to monitor the emergence of discussions on public issues, extremely synchronized with events and news – which is, moreover, a feature of use of this platform. The coronavirus hashtag was chosen as a mechanism to track the development of Italian reactions, following the evolution of its sense and sensemaking and considering it as a polysemic collector. The aim is to identify within the tweets the actors, the topics, and the tone of the debate in an open public space. Furthermore, the analysis is carried out in search of the Italians’ perception of the lockdown and whether they are in favor of it because of the defense of public health or they see it as a restriction of their individual freedom. The analysis, which used the socio-constructivist approach of Emotional Text Mining, reveals two explanatory-dimensions in the governance of the crisis: lockdown and breakdown and allows us to understand the reasons for Twitter’s instinct-reactions.